Rudolph Ganz, patriotism, and standardization of the Star-Spangled Banner, 1907-1958 - Quinn, Iain, 1973- author.
1 online resource (90 pages)
Keywords: "This book examines the succession of events towards the potential standardization of the music for the 'Star-Spangled Banner' from an initial letter to President Roosevelt in 1907 to the 1958 congressional hearings on the National Anthem, and the later work of the Swiss-Born American pianist, Rudolph Ganz. These events took place across five decades when a culture of public patriotism was especially pronounced for immigrant musicians. This book contextualizes the complementary experiences of a leading immigrant musician, Ganz, who successfully navigated the world of public patriotism while pursuing the realization of a standardized version. The materials are discussed through the lens of the performance practice. The legacy of standardization has not previously been examined. The response and actions of an immigrant, Ganz, in a culture of necessary patriotism for foreign-born artists sheds important new light on this topic. It demonstrates the challenges, fears, and cultural expectations regarding standardization of an important patriotic work"--